2000
DOI: 10.1054/bjoc.2000.1281
|View full text |Cite
|
Sign up to set email alerts
|

Differential and antagonistic effects of 9-cis-retinoic acid and vitamin D analogues on pancreatic cancer cells in vitro

Abstract: Retinoids and vitamin D are known to exert important anti-tumour effects in a variety of cell types. In this study the effects of 9- cis -retinoic acid (9cRA) the vitamin D analogues EB1089 and CB1093 on three pancreatic adenocarcinoma cell lines were investigated. All compounds caused inhibition of in vitro growth but the vitamin D analogues were generally the more potent growth inhibitors. They were also more effective on their own than in combination with 9cRA. Growth arrest correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 42 publications
(38 reference statements)
0
33
1
1
Order By: Relevance
“…Moreover, authentic retinoid receptor-interacting ligands, including all-trans retinoic acid, also induce caspase-associated apoptosis in pancreatic cancer cells (Fujimoto et al, 1999;Pettersson et al, 2000Pettersson et al, , 2001. Some studies also show that an altered Bcl-2/Bax ratio, in favor of Bax, is associated with RRM-dependent cell death (Pettersson et al, 2000). However, the Bcl-2/Bax ratio was not observed to change in the present studies, suggesting that this change is not necessary for the effects of AGN193198.…”
Section: Role Of Apoptosiscontrasting
confidence: 41%
See 1 more Smart Citation
“…Moreover, authentic retinoid receptor-interacting ligands, including all-trans retinoic acid, also induce caspase-associated apoptosis in pancreatic cancer cells (Fujimoto et al, 1999;Pettersson et al, 2000Pettersson et al, , 2001. Some studies also show that an altered Bcl-2/Bax ratio, in favor of Bax, is associated with RRM-dependent cell death (Pettersson et al, 2000). However, the Bcl-2/Bax ratio was not observed to change in the present studies, suggesting that this change is not necessary for the effects of AGN193198.…”
Section: Role Of Apoptosiscontrasting
confidence: 41%
“…This is perhaps not surprising, since, as outlined above, apoptosis is a hallmark of the mechanism of RRM action. Moreover, authentic retinoid receptor-interacting ligands, including all-trans retinoic acid, also induce caspase-associated apoptosis in pancreatic cancer cells (Fujimoto et al, 1999;Pettersson et al, 2000Pettersson et al, , 2001. Some studies also show that an altered Bcl-2/Bax ratio, in favor of Bax, is associated with RRM-dependent cell death (Pettersson et al, 2000).…”
Section: Role Of Apoptosismentioning
confidence: 99%
“…We have shown that they can also act as potent apoptosis-inducers (Pettersson et al, 2000), and in this study we have further elucidated the mechanisms behind this finding.…”
Section: Discussionmentioning
confidence: 52%
“…A phase II trial of 13-cis retinoic acid and interferon-a in patients with advanced pancreatic carcinoma has also been completed and promising results with one partial remission and 14 out of 22 patients with stable disease for a median duration of 5 months were reported (Brembeck et al, 1998). We have shown that ATRA and 9cRA induce apoptosis in a number of pancreatic adenocarcinoma cell lines and enhance the cytotoxic effects of chemotherapeutic agents in these cells (Pettersson et al, 2000(Pettersson et al, , 2001. In the present study, we examined the role of two families of proteins that are important players in many apoptotic responses, the Bcl-2 proteins and caspases.…”
mentioning
confidence: 87%
“…In vivo studies in animal models have shown that seocalcitol can cause regression of established tumours, prevent the development of metastases, and prolong survival time in tumour-bearing animals (Colston et al, 1992(Colston et al, , 1997James et al, 1998;Lokeshwar et al, 1999;Nickerson and Huynh, 1999), with significant inhibition of tumour progression achieved at doses that do not cause significant hypercalcaemia (Colston et al, 1992). Furthermore, seocalcitol inhibits growth of pancreatic cancer cells in vitro (Zugmaier et al, 1996;Pettersson et al, 2000) and inhibits growth in vivo of pancreatic cancer xenografts in immunodeficient mice (Colston et al, 1997). Seocalcitol was well tolerated in a phase I clinical study in patients with breast or colorectal cancer, with dose-dependent hypercalcaemica (Gulliford et al, 1998).…”
mentioning
confidence: 99%